Information and Communication Technologies for managing frailty: a systematic literature review - Quiroga Torres, Daniel Alejandro; Cruz, Antonio Miguel; Monsalve, Laura; Ladurner, Anna-Maria; Jaime, Luisa Fernanda; Wang, Daniel (International Society on Aging and Disease, 2020)
Frailty is a prevalent condition among Canadians; over one million are diagnosed as medically frail, and in the next ten years this number will double. Information and telecommunication technologies can provide a low-cost method for managing frailty more proactively. This study aims to examine the range and extent of information and telecommunication technologies for managing frailty in older adults, their technology readiness level, the evidence, and the associated outcomes. A systematic literature review was conducted. Four databases were searched for studies: Medline, EMBASE, CINAHL, and Web of Science. In total, we included 19 studies (out of 9,930) for the data abstraction. Overall, our findings indicate that (1) the proposed frailty phenotype is the most common ground truth to be used for assessing frailty; (2) the most common uses of information and telecommunication technologies for managing frailty are detection, and monitoring and detection, while interventional studies on frailty are very rare; (3) the five main types of information and telecommunication technologies for managing frailty in older adults are information and telecommunication technology-based platforms, smartphones, telemonitoring (home monitoring), wearable sensors and devices (commercial off-the-shelf), and multimedia formats for online access; (4) the technology readiness level of information and telecommunication technologies for managing frailty in older adults is the “Technology Demonstration” level, i.e., not yet ready to be operated in an actual operating environment; and (5) the level of evidence is still low for information and telecommunication technology studies that manage frailty in older adults. In conclusion, information and telecommunication technologies for managing frailty in the older adult population are not yet ready to be full-fledged technologies for this purpose.

La fragilidad es una condición prevalente entre los canadienses; más de un millón son diagnosticados como médicamente frágiles, y en los próximos diez años este número se duplicará. Las tecnologías de la información y las telecomunicaciones pueden proporcionar un método de bajo coste para gestionar la fragilidad de forma más proactiva. Este estudio tiene como objetivo examinar la gama y el alcance de las tecnologías de la información y las telecomunicaciones para la gestión de la fragilidad en los adultos mayores, su nivel de preparación tecnológica, la evidencia y los resultados asociados. Se realizó una revisión sistemática de la literatura. Se buscaron estudios en cuatro bases de datos: Medline, EMBASE, CINAHL y Web of Science. En total, se incluyeron 19 estudios (de 9.930) para la extracción de datos. En general, nuestros resultados indican que (1) el fenotipo de fragilidad propuesto es la verdad básica más comúnmente utilizada para evaluar la fragilidad; (2) los usos más comunes de las tecnologías de la información y las telecomunicaciones para gestionar la fragilidad son la detección, y la monitorización y detección, mientras que los estudios de intervención sobre la fragilidad son muy raros; (3) los cinco tipos principales de tecnologías de la información y las telecomunicaciones para la gestión de la fragilidad en los adultos mayores son las plataformas basadas en la tecnología de la información y las telecomunicaciones, los teléfonos inteligentes, la telemonitorización (seguimiento en el hogar), los sensores y dispositivos portátiles (comerciales), y los formatos multimedia para el acceso en línea; (4) el nivel de preparación tecnológica de las tecnologías de la información y las telecomunicaciones para la gestión de la fragilidad en los adultos mayores es el nivel de "Demostración de Tecnología", es decir. e., (5) el nivel de evidencia es todavía bajo para los estudios de las tecnologías de la información y las telecomunicaciones que gestionan la fragilidad en los adultos mayores. En conclusión, las tecnologías de la información y las telecomunicaciones para gestionar la fragilidad en la población de adultos mayores aún no están listas para ser tecnologías de pleno derecho para este propósito.
Keywords: Tenologías de la información; Telecomunicaciones; Adultos mayores; Information and telecommunication technologies; Frail; Fragility; Frail older adults; Tecnologías de la información y las telecomunicaciones; Frágiles; Fragilidad; Adultos mayores frágiles